Why toast lands jelly-side down : Zen and the art of physics demonstrations - Ehrlich, Robert, 1938- (Princeton, N.J. : Princeton University Press, 1997)
Contains demonstrations and experiments designed to show how the principles of physics relate to everyday objects, covering Newton's laws, fluids, electricity and magnetism, optics, and other topics; and includes information on how to design physics demonstrations.
Includes bibliographical references (p. [193]-194) and index.
The Science Teacher (N.S.T.A.).
Adult
Keywords: Physics -- Experiments; Physics -- Experiments